Hypercellular Mucinous Carcinoma Resembling Invasive Cribriform Carcinoma and Hypocellular Mucinous Carcinoma of the Breast; A Rare Case with Unique Association - Hideki Mori; Yuichiro Okubo; Yoshimi Iriguchi; Takahiro Mase (Medical – Clinical – Research, 2026)
75-years-old Japanese woman developed a breast tumor with approximate size of 60 mm. The tumor consisted of two lesions. The main neoplasm was made up of invasive epithelial islands with cribriform pattern resembling invasive cribriform carcinoma. Immunohistochemistry of CK-7-positive and CK-14 negative also supported such diagnosis of the cribriform carcinoma. However, 30% of the tumor cells was found to display positive expression of synaptophysin indicating that the tumor had neuroendocrine differentiation. Furthermore, a small amount of intracellular mucin accumulation was proved by Alcian blue staining in the tumor cells. Thus, the tumor was judged as a hypercellular mucinous carcinoma (MC) (type B MC). Another tumor demonstrated a histological pattern of hypocellular mucinous carcinoma (type A MC) with abundant mucin accumulation. According to the WHO classification of mucinous breast cancer (MBC) (2019), present type A MC corresponds to the pure type (PMBC), and the main neoplasm will be equivalent to the mixed type (MMBC) with special variant of cribriform pattern. To the best of our knowledge, such case with unique association of two types of MCs of the breast will be exceedingly rare, and valuable for recognition of mutual association of both types of MC and mucinous pathways of the tumorigenesis of MC.